Effect of Moringa oleifera Leaf Powder Biscuits on Blood Cholesterol Levels in Patients with Hypercholesterolemia at the Kutablang Community Health Center, Bireuen Regency - Cut Eka Handayani; Nunung Sri Mulyani (JAND: Journal of Applied Nutrition and Dietetic, 2026)
Hypercholesterolemia is a major risk factor for cardiovascular disease and is characterized by elevated blood cholesterol levels. Moringa oleifera leaves are rich in dietary fiber, polyphenols, flavonoids, and phytosterols that have been reported to improve lipid metabolism and may contribute to cholesterol reduction. This study aimed to evaluate the association between the consumption of Moringa oleifera leaf powder biscuits and total blood cholesterol levels among patients with hypercholesterolemia. A quasi-experimental study using a one-group pretest–posttest design was conducted from July 1 to July 7, 2025, at the Kuta Blang Community Health Center, Bireuen Regency, Indonesia. Sixteen patients with hypercholesterolemia who met the inclusion criteria were recruited using purposive sampling. Participants consumed three Moringa oleifera leaf powder biscuits daily for seven consecutive days. Total blood cholesterol levels were measured before and after the intervention. Data were analyzed using the paired-samples t-test with a significance level of p < 0.05. The mean total cholesterol level decreased significantly from 272.75 ± 45.24 mg/dL before the intervention to 241.38 ± 45.99 mg/dL after the intervention, representing a mean reduction of 31.37 mg/dL (t = 7.057, p < 0.001). Consumption of Moringa oleifera leaf powder biscuits for seven days was associated with a significant reduction in total blood cholesterol levels among patients with hypercholesterolemia. These findings suggest that Moringa oleifera leaf powder biscuits may have potential as a functional food to support dietary management of hypercholesterolemia. Further randomized controlled studies with larger sample sizes and longer intervention periods are recommended to confirm these findings.